The use of LMS Moodle to Improve Reading Comprehension Skill for the 10th Grade Students - Oetomo, Tyas; Musyarofah, Lailatul; Widodo, J. Priyanto (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this research was to increase students' achievement in reading comprehension by implementing the LMS Moodle to the 10th grade students at SMA Petra 4 Sidoarjo in the academic year 2020/2021. Classroom Action Research (CAR) was applied in conducting this study from January to June 2021. Each cycle of CAR consisted of four steps: planning, action, observation, and reflection. The data were gathered through the use of two instruments: observation and test. The results indicated that students made great progress in their ability to comprehend the reading texts. Pre-test mean score was only 72.71, but improved to 79.29 in cycle 1 and 86.57 in cycle 2. The lowest pre-test score was only 65 and improved to 70 to 75 in subsequent cycles. Meanwhile, the highest pre-test score was 82.5, and the highest post-tests scores were 92.5 and 95. In case of the students who passed the tests, while only 9 students (25.71%) passed the pre-test, there were significant improvements in post-tests, with 21 students (60%) passing in post-test cycle 1 and 33 students (94.29%) passing in post-test cycle 2. This research was stopped in cycle 2 due to the fact that the criteria for success were met in a percentage of 94.29%, with 33 students passing the post-test in cycle 2, based on the Minimum Mastery Criteria (KKM) standard of > 76